INFLUENCERS AND CONTENT MARKETING AS THE MAIN DRIVERS OF PURCHASE DECISIONS AT BAKSO O'BOSS, BENGKULU CITY - Muhammad Riski Minandar; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to identify influencers and content marketing as drivers of consumer purchasing decisions at Bakso O'Boss in Bengkulu City. The study uses a quantitative approach with multiple linear regression methods to analyze data obtained from consumers. The results of the analysis show that partially the influencer variable has a positive and significant influence on purchasing decisions, as evidenced by the value> ttable (2,730>1.73406)and Sig level<alpha0.05 = (0.001 < 0.05). The content marketing variable also has a positive and significant influence on purchasing decisions with a value of> ttable (4.453>1.73406) and Sig<alpha0.05 = (0.012 < 0.05).Simultaneously, influencers and content marketing have a significant effect on purchasing decisions, with a calculated F value (16.304) > F table (3.55) and significance (0.000 < 0.05). This study concludes that collaboration between influencers and effective content marketing strategies can increase product appeal and drive consumer purchasing decisions.